Effect of High-Fat and Low-Fat Dairy Products on Cardiometabolic Risk Factors and Immune Function in a Low Birthweight Swine Model of Diet-Induced Insulin Resistance - She, Yongbo; Wang, Kun; Makarowski, Alexander; Mangat, Rabban; Tsai, Sue; Willing, Benjamin P.; Proctor, Spencer D.; Richard, Caroline (Frontiers in Nutrition, 2022)
Although dairy intake has been shown to have a neutral or some beneficial effect on major cardiometabolic risk factors, the impact of dairy, and especially dairy fat, on immune function remains to be investigated. To understand the effect of consuming dairy fat on cardiometabolic risk factors and immune function, we used an established low birthweight (LBW) swine model of diet-induced insulin resistance to compare high-fat and low-fat dairy products to a control high-fat diet (CHF). LBW piglets were randomized to consume one of the 3 experimental HF diets: 1) CHF, 2) CHF diet supplemented with 3 servings/day of high-fat dairy (HFDairy) and 3) CHF diet supplemented with 3 servings/day of low-fat dairy (LFDairy). As comparison groups, normal birthweight (NBW) piglets were fed a CHF (NBW-CHF) or standard pig grower diet (NBW-Chow). A total of 35 pigs completed the study and were fed for a total of 7 weeks, including 1 week of CHF transition diet. At 12 weeks of age, piglets were euthanized. Fasting blood and tissue samples were collected. Ex vivo cytokine production by peripheral blood mononuclear cells (PBMCs) stimulated with pokeweed (PWM), phytohemagglutinin (PHA) and phorbol myristate acetate-ionomycin (PMA-I) were assessed. As expected, LBW-CHF piglets showed early signs of insulin resistance (HOMA-IR, P model = 0.08). Feeding high-fat dairy products improved fasting plasma glucose concentrations more than low-fat dairy compared to LBW-CHF (P < 0.05). Irrespective of fat content, dairy consumption had neutral effect on fasting lipid profile. We have also observed lower production of IL-2 after PWM and PHA stimulation as well as lower production of TNF-α and IFN-γ after PWM stimulation in LBW-CHF than in NBW-Chow (all, P < 0.05), suggesting impaired T cell and antigen presenting cell function. While feeding high-fat dairy had minimal effect on immune function, feeding low-fat dairy significantly improved the production of IL-2, TNF-α and IFN-γ after PWM stimulation, IL-2 and IFN-γ after PHA stimulation as well as TNF-α after PMA-I stimulation compared to LBW-CHF (all, P < 0.05). These data provide novel insights into the role of dairy consumption in counteracting some obesity-related cardiometabolic and immune perturbations.